2011
DOI: 10.1111/j.1468-2311.2011.00677.x
|View full text |Cite
|
Sign up to set email alerts
|

Ten Years of Monitoring Illicit Drug Use in Prison Populations in Europe: Issues and Challenges

Abstract: The European Monitoring Centre for Drugs and Drug Addiction (EMCD-DA) has been collecting aggregated data on illicit drug use among European prison populations for over a decade. Additional studies were identified in a literature search. Together, these sources yielded 53 studies reporting data during the period 2000 to 2008. Analysis of these studies reveals that the available data are scarce and patchy, with large variations in methodology. This diversity hampers comparison, and may, in part, account for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…The number of prisoners with a psychiatric diagnosis of substance use may thus be underestimated, especially for men, given their greater numbers. The heterogeneity of data on substance abuse in prison underscores the challenge of obtaining an accurate prevalence of drug use/misuse in the prison population [ 38 ], especially when some prisoners hide their dependencies to avoid sanctions [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of prisoners with a psychiatric diagnosis of substance use may thus be underestimated, especially for men, given their greater numbers. The heterogeneity of data on substance abuse in prison underscores the challenge of obtaining an accurate prevalence of drug use/misuse in the prison population [ 38 ], especially when some prisoners hide their dependencies to avoid sanctions [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…7 A study of drug use in prison in the European Union, found that reported rates of ever having injected drugs in prisons among the countries providing data were in the range of 15–30%. 204 While some PWUD before serving a prison sentence will discontinue or reduce their use in prison or change their method of use, some people will seek to maintain drug use, including drug injection, or will begin using drugs while in prison. 205 In addition to drug-related risk, PWUD in prison face HIV risks associated with unprotected sex, sexual violence, and unsafe tattooing.…”
Section: Drug-related Incarceration and Healthmentioning
confidence: 99%
“…The challenges in accurately measuring prison substance use have been recognised in both Australia and overseas [1,13–15]. Calls have been made to implement a standardised monitoring tool so that national and international comparisons of substance use can be carried out [1].…”
Section: Introductionmentioning
confidence: 99%